Reproductive effects linked to DNA methylation in male zebrafish chronically exposed to environmentally relevant concentrations of di-(2-ethylhexyl) phthalate. (June 2018) - Ma, Yan-Bo; Jia, Pan-Pan; Junaid, Muhammad; Yang, Li; Lu, Chun-Jiao; Pei, De-Sheng
Abstract: Di-(2-ethylhexyl) phthalate (DEHP) possesses the potential to interfere with the male reproductive endocrine system in mammals; however, its reproductive toxicity in male zebrafish and associated epigenetic studies have not been explored. In this study, three-month-old male zebrafish were exposed to environmentally relevant concentrations of DEHP (0, 10, 33 and 100 μg/L) for 3 months, and then the impact on the reproduction of males and the underlying mechanism were investigated. Histological testing showed that an exposure concentration of 100 μg/L DEHP significantly inhibited spermatogenesis, with an associated decline in capability to fertilize untreated oocytes. Electron microscopic examinations also revealed noticeable damage to the testicular ultrastructure at the 100 μg/L DEHP exposure level. In addition, exposure to 33 and 100 μg/L of DEHP resulted in a decline of circulating testosterone (T) and an increase in the level of 17β-estradiol (E2), both of which were possibly derived from the downregulation of cyp17a1 and hsd17b3 genes and the upregulation of the cyp19a1a gene in the gonads. The DNA methylation statuses of these genes were altered within their promoter regions. A significant increase in global DNA methylation in both the male testes and their offspring larvae was observed at higher exposure concentration of DEHP. Our findings demonstrate that exposure to environmentally relevant concentrations of DEHP can damage the testes, disturbe the sex hormones production, and inhibite spermatogenesis, which ultimately impairs the reproduction of male zebrafish. Graphical abstract: Image 1 Highlights: Investigation of long-term DEHP effects on male reproduction in zebrafish. DEHP inhibited spermatogenesis and affected the gene-specific DNA methylation of cyp17a1, hsd17b3 and cyp19a1a in male. DEHP increased the global DNA methylation both in male and their offspring. Abstract : This study highlights the reproductive toxicity of chronic exposure to DEHP with environmentally relevant concentrations on male zebrafish.